2021
DOI: 10.3390/ijerph18147524
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety in the Eyes of Aspiring Healthcare Professionals: A Systematic Review of Their Attitudes

Abstract: A culture of safety is important for the delivery of safe, high-quality care, as well as for healthcare providers’ wellbeing. This systematic review aimed to describe and synthesize the literature on patient safety attitudes of the next generation of healthcare workers (health professional students, new graduates, newly registered health professionals, resident trainees) and assess potential differences in this population related to years of study, specialties, and gender. We screened four electronic databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…On the basis of the commonalities among surveys, we grouped the results from these studies into seven patient safety culture dimensions, as shown in Fig. 4 [26].…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the commonalities among surveys, we grouped the results from these studies into seven patient safety culture dimensions, as shown in Fig. 4 [26].…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…The extracted data were synthesized in a simple manner. Attitude was considered highly positive if the article reported the score as positive or having a scale score > 75; attitude was considered positive/desirable if an item had a mean score > 3 on a 5-point Likert scale or > 4 on a 7-point Likert scale, i.e., "strongly agree," "agree," or "somewhat agree" [22,26].…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes towards patient safety correspond to the beliefs and values that professionals have on the perception of security in their workplace. Students and professionals in their first steps usually show more positive attitudes regarding patient security in areas such as teamwork, error inevitability, and the presence of specific curricular training on patient security [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that patient safety is crucial for delivering high-quality care [ 26 ], aspiring healthcare providers should be supported in acquiring adequate patient safety skills [ 27 , 28 , 29 ]. To better understand patient safety attitudes among young healthcare workers and healthcare profession students, Tocco-Tussardi et al [ 30 ] synthesized the existing literature and concluded that this population shows overwhelmingly positive attitudes in certain domains, such as teamwork climate and error inevitability but more negative perceptions in other areas, such as safety climate and disclosure responsibility. The authors urge health professions educators and institutions to create a learning culture by integrating patient safety education and training in the curricula of aspiring healthcare professionals and to guarantee that the influential hidden curriculum better reflects the elements of the explicit curriculum.…”
mentioning
confidence: 99%